Review of Medical Physiology - Ganong, William F (Boston McGraw-Hill, 2005)
This work provides an overview of mammalian and human physiology. Examples from clinical medicine have been integrated throughout the chapters to show important physiologic concepts. It features content summaries, objectives, essay questions and multiple-choice questions.
Include Index, Appendix and Illustrations.
Keywords: Physiology -- Problems -- Human Physiology